Burnout among surgical residents in a lower-middle income country – Are we any different? - Malik, Awais Amjad (Ann Med Surg (Lond), 2016)
OBJECTIVE: To assess the presence of burnout among surgical residents working at various public sector hospitals in Pakistan. DESIGN: A survey based on MBI was used to assess the presence of burnout. Residents were grouped into Group A (Burn out) or Group B (No burn out). Pearson Test was used to see any correlation between different variables and burn out. A p value of <0.05 was taken as significant. SETTING/PARTICIPANTS: A cross sectional survey of all the surgical residents at various public sector hospitals in Lahore was done. RESULTS: A total of 133 residents responded to our questionnaire. 74% respondents were male and 26% were female. All residents showed a very high level of burnout. 50.4% residents had high levels of burn out on the EE category, 49.6% in the DP category and 53.4% residents had low levels on the PA scale. When assessed for overall burn out 57.9% residents had overall burnout. Males were more prone to develop burnout. Job dissatisfaction was the most prevalent reason for burn out. Owning a smartphone was significantly associated with development of burnout. Awareness regarding the burnout syndrome and having children were two factors which had a protective effect against burnout syndrome. Marriage, working hours, financial conditions, smoking and consumption of coffee/tea had no effect on development of burnout syndrome. CONCLUSION: There is high prevalence of burnout among the surgical residents in our hospitals. Unsatisfactory training is the number one reason for development of this syndrome.